Skin health promoting effects of a proprietary nutraceutical ingredient (SesZen-BioTM): a placebo controlled, double-blind, and randomized clinical study - Upadhyay, Ratna; Gadani, Mihir C.; Badak, Sneha (International Journal of Research in Dermatology, 2024)
Background: This study evaluated the skin health benefits of SesZen-BioTM, a 0.5% natural biotin supplement derived from Sesbania grandiflora, previously linked to hair growth, in healthy adults aged 30-55 with mild skin ageing. Methods: In a single-center, double-blind, placebo-controlled trial, participants between ages 30-55 years with mild skin ageing received either SesZen-BioTM or a placebo, with assessments conducted on days 0, 28, and 56. Parameters measured included facial wrinkles, fine lines, skin elasticity, hydration, skin barrier function and overall skin health. Results: Significant reduction (p<0.01) in crow’s feet area by 27.11% (day 28) and 48.14% (day 56) and 17.95% and 51.17% reduction in fines lines were observed in the treatment group as compared to 12.1% reduction for placebo group at day 56. Physician global assessment (PGA) scores showed improvement in skin condition by 14.07% (day 28) and 20.58% (day 56) for SesZen-BioTM treatment group. The facial skin tone assessment described by individual typology angle (ITA) showed lighter skin tone by 30.55% (day 28) and 58.23% (day 56) (p<0.01). Treatment group showed decrease in retraction time for skin elasticity on day 56, decreased skin roughness and increased skin hydration. Both groups showed decreased transepidermal water loss (TEWL) on both visits (days 28 and 56) as compared to baselines (p<0.01). The placebo group showed no improvement in PGA score, skin tone lightness (L*) and ITA score, skin hydration, or skin elasticity. Conclusions: SesZen-BioTM appears to effectively promote skin health, reducing fine lines and improving skin tone, elasticity, and hydration, suggesting a viable strategy for combating skin aging and enhancing overall skin appearance.